SISTEM MONITORING PAKAN DAN MINUM KUCING INDOOR BERBASIS IOT MENGGUNAKAN FUZZY LOGIC - Anang Budikarso; Kalya Tsabita; Faridatun Nadziroh, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Cats are one of the most popular pets. However, owners often find it difficult to monitor their cat's food and drink intake which can lead to an irregular diet and potentially cause illness and death. This research designs an IoT based cat food and drink monitoring system that allows cat owners to provide food and drink to their cats easily. This system uses a RTC module to automatically control feeding times and can be monitored via a smartphone. Data from the ESP32 microcontroller is sent to the server using the MQTT communication protocol with the Node-RED platform. The fuzzy logic method is applied to ensure the cat's feeding and drinking is not excessive. The results show the system can work with proper data synchronization between MQTT and sensors with an average error obtained of 1.80% for the feed section and 3.69% for the drinking section and an average delay of 2 seconds in the feed section and 25.7 seconds in the drinking section. Overall, the system performed well and reliably in managing the cat's food and drink intake.